MOODLE-BASED DIGITAL INTERACTIVE BOOK: STUDENT REFLECTIONS ON THE TECHNOLOGY INTEGRATED BLENDED CLASS - Lungguh Halira Vonti; Abdul Rosyid; Poppy Sofia Hidayati (University of Kuningan, 2023)
Online learning has been going on for almost 2 years now since pandemic and caused a dramatic change of education, with the rise of e-learning, where teaching takes place remotely and using a variety of digital platforms. One of the challenges is access internet and technology used in digital learning that forced the lecturers to innovate in providing a learning approach or using innovative teaching media as well as teaching material to facilitate students in the learning process independently wherever they are. The shift away from the education system caused by the COVID-19 pandemic raises the question of whether the adoption of online learning will continue post-pandemic, and how such a shift will impact education systems around the world. This study proposed some of the objective due to the recent condition of the education field. One of the objectives is to describe the students-teacher reflection toward the implementation of digital interactive book in their class. The study employed a descriptive analysis research design and gained the data from semi structured interview and questionnaire. The participant of this study was a class studying Grammar subject in a blended class of a second year at a higher educational institution (FKIP) in Universitas Pakuan. The result of the study showed that somehow, the students have positive reflections toward the use of digital interactive book designed by the researchers.